Transformation of Digital Legal Deposit in Terms of Legislation and Public Access - Alexandrov, Georgi (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian]The age of digitization is marked by a huge quantity and variety of electronic content distributed on the Internet. Building national collections of deposited electronic publications is a challenge related to the preservation of the global cultural heritage. The purpose of the article is to examine the ongoing transformation of the digital legal deposit with a focus on the legislative and public access regulation. The geographical scope of the research covers the countries from the European Union in the time span of the last two decades. Three stages of digital legal deposit implementation are identified: legislative regulation, technological infrastructure and practical procedures. The article presents the adaptation of deposit laws to the new media environment marked by fast growing online publishing. The study identifies the features of controlled e-reading as the main access tool in the deposit institutions and classifies them into two types: restriction related and usability related. The major challenges to a further digital legal deposit development are specified as legislative, technological, financial, and social. Examples of public access regulation in several European national libraries are observed with emphasis on the most advanced practices. Based on the main findings, the article formulates the forecast for less restrictions and better cooperation within the European Union concerning the regulation of public access to digital deposit collections.
Keywords: digital legal deposit, electronic publications, e-reading, deposit institutions, public access